IMPLEMENTASI FUZZY LOGIC UNTUK PENGATURAN KELEMBAPAN TANAH PADA TANAMAN SAWI BERBASIS INTERNET OF THINGS (IOT) - Pagala, J. Rifaldo; Santa, Kristofel; Kainde, Quido C. (LPPM Unbaja, 2024)
The soil moisture regulation system in mustard plants is an important part of ensuring optimal plant growth. In this study, we tested a soil moisture regulation system using fuzzy logic over a 7-day period. The test was carried out by watering in the morning and evening, according to the needs of mustard plants which require soil moisture to be maintained in the range of 50-70%. Soil moisture data was taken at 6:00 am and 4:30 pm using a soil moisture sensor. Tests were also conducted using Blynk software to visually monitor soil moisture. The test results show that the system is able to adjust the watering duration based on the measured soil moisture, in accordance with the rules set in fuzzy logic. Although there are variations in soil moisture every day, the system can still function well in maintaining soil moisture in the desired range